Analysis of Factors Affecting Medical Cost and Insurance Reimbursement Gaps in Hypertension Heart Failure Patients - Suri, Nurma; Kylalona, Gracylia (Jurnal Jaminan Kesehatan Nasional, 2025)
Hypertension with congestive heart failure (CHF) results in high disease-related costs, placing a burden on patients, families, and healthcare facilities. Direct medical costs are known to be the highest proportion. This study aims to identify factors associated with direct medical costs in patients with hypertension and CHF and the difference in payment amounts compared to insurance reimbursements. This research uses a cross-sectional design at Hospital X in Lampung Province. The study population consists of patients diagnosed with hypertension and CHF within the period 2020-2022, with samples selected using total sampling. From 101 samples, the total direct medical cost for all cost components was IDR 908,700,216, with an average direct medical cost of IDR 8,997,032. The highest cost component was cardiac catheterization, with a total IDR of 473,081,000 and an average IDR of 36,390,846. The lowest cost component was additional medical expenses, with a total IDR 16,348,780 and an average IDR 166,824. Bivariate analysis showed a significant relationship between direct medical costs and length of hospital stay, insurance classes, and comorbid conditions. In addition, bivariate analysis showed a significant difference between direct medical costs and insurance reimbursement, with a positive discrepancy of IDR 4.437.619. This study concludes that length of stay, insurance classes, and comorbidities are significantly associated with direct medical costs. There is also a significant difference between direct medical costs and the amount of insurance reimbursement.